1982
DOI: 10.1128/aem.43.4.899-904.1982
|View full text |Cite
|
Sign up to set email alerts
|

Comparative antimicrobial activity, in vitro and in vivo, of soft N-chloramine systems and chlorhexidine

Abstract: Antimicrobial activity of the following four new N-chloramine compounds was evaluated: two chlorinated simple amino acids, a chlorinated half-ester of succinic acid, and a chlorinated half-ester of glutaric acid. For comparison, the known bactericidal agents 3-chloro-4,4-dimethyl-2-oxazolidinone and chlorhexidine were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…At a coricentration of 0.1%, but not at 0.005%, an organic enrichment had no appreciable effect on microbicidal activity. Selk et al (20) reported that the loss of activity of N-chloramine compounds in the presence of 5% serum was negligible when the concentration of the N-chloramine was 1,000 ,ug/ml or higher. The inhibitory activity of N-chloramine, although impressive for bacteria, was less for fungi than the action reported for other disinfectants such as iodine and hydrogen peroxide (18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a coricentration of 0.1%, but not at 0.005%, an organic enrichment had no appreciable effect on microbicidal activity. Selk et al (20) reported that the loss of activity of N-chloramine compounds in the presence of 5% serum was negligible when the concentration of the N-chloramine was 1,000 ,ug/ml or higher. The inhibitory activity of N-chloramine, although impressive for bacteria, was less for fungi than the action reported for other disinfectants such as iodine and hydrogen peroxide (18).…”
Section: Resultsmentioning
confidence: 99%
“…Their inhibitory activities are of a broad spectrum, including interference with both glucose oxidation and ionic exchange and the disruption of the cell membrane (9,16). Recently Selk et al (20) recommended N-chloramine compounds for use in topical drugs for humans as an alternative to chlorhexidine. Two N-chloramine compounds, a chlorinated simple amino acid (II-A) and a chlorinated half-ester of succinic acid (III-A), both at concentrations of 0.1% or less, reduced bacterial inocula of 104 cells per ml in buffered sodium acetate (pH 4.5) to nearly 0 in 15 min.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chloramine-T â is bactericidal (38,39). N-chloramines exhibit low toxicity and skin irritation and are superior to chlorhexidine in preventing the expansion of the normal skin flora in vivo (40). Chloramine-T â is better than HOCl in inactivation of Staphylococcus aureus (41) and monochloramine is superior to N-chlorotaurine in inactivation of Mycobacterium terrae (42).…”
Section: Ad (A)mentioning
confidence: 99%
“…CHX is widely studied and is a proven gold standard for oral antiseptics (13). The cationic bis‐biguanide has a widespread antibacterial activity and a high affinity to attach to the skin and mucosae (14–17).…”
Section: Introductionmentioning
confidence: 99%